An analysis of factors which contribute to loan deliquency among small medium enterprises : The case of National Microfinance Bank Plc - Malundila, Farida Msham (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirement for award of the Degree of Masters of Marketing Management of Mzumbe University